2016
DOI: 10.3906/biy-1501-67
|View full text |Cite
|
Sign up to set email alerts
|

Salinity effects on expression of some important genes in sensitiveand tolerant grape genotypes

Abstract: Recent studies have shown that application of salt stress induced massive changes in grapevine gene expression (Vincent et al., 2007;Jellouli et al., 2008). Comparative gene expression analysis could be a useful approach for understanding the mechanisms of tolerance and susceptibility (Kozian and Kirschbaum, 1999).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…The synthesis of phenolic metabolites is considered to be as one of the first counter measures to maintain the redox homoeostasis in a plant's response to oxidative stress. For instance, an affinity towards up-regulation of PAL genes was observed in tolerant genotype of grapevines (Vitis vinifera L.) to 50 mM NaCl, highlighting the strong relation between the enhancement of the expression profile of PAL and the degree of plant salinity tolerance (Mohammadkhani et al 2016). In the same way, Yan et al 2016 revealed that salt (150 mM and 300 mM NaCl) enhanced chlorogenic acid synthesis in honeysuckle plants (Lonicera japonica Thunb.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of phenolic metabolites is considered to be as one of the first counter measures to maintain the redox homoeostasis in a plant's response to oxidative stress. For instance, an affinity towards up-regulation of PAL genes was observed in tolerant genotype of grapevines (Vitis vinifera L.) to 50 mM NaCl, highlighting the strong relation between the enhancement of the expression profile of PAL and the degree of plant salinity tolerance (Mohammadkhani et al 2016). In the same way, Yan et al 2016 revealed that salt (150 mM and 300 mM NaCl) enhanced chlorogenic acid synthesis in honeysuckle plants (Lonicera japonica Thunb.…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory and field conditions, thePistacia vera scions, grown on several Pistacia spp.rootstocks, can tolerate sodium chloride (NaCl) concentrations of up to 150 mM (Walker et al, 1987;Ferguson et al, 2002). In contrast, citrus, grape, and avocado are all characterized as relatively salinity sensitive tree crops, and grape and avocado can only tolerate up to 50 mM and 15 mM NaCl respectively (Bernstein et al, 2004;Mohammadkhani et al, 2016;Ahmad and Anjum, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, VvChS and VvPAL transcripts significantly increased only in the leaves of tolerant genotypes. 111 A total of 209 and 36 differentially expressed transcripts were identified in salt tolerant Kalamon and salt sensitive Chondrolia Chalkidikis olive cultivars in response to NaCl stress. In Kalamon, all the transcripts were significantly down regulated in the post-stress period.…”
Section: Transcriptomicsmentioning
confidence: 99%